Anatomical validation of middle cerebral artery position as identified by transcranial pulsed Doppler ultrasound. Issue 9 (September 1986) - Gillard, J H; Kirkham, F J; Levin, S D; Neville, B G; Gosling, R G
Abstract : The basal cerebral arteries were insonated using transcranial pulsed Doppler ultrasound (TPDU) at 2 MHz. The Doppler sample volume (SV) depths at which signals were obtained which could be attributed to the middle, anterior and posterior cerebral arteries (MCA, ACA and PCA) were compared with measurements in adult cadavers and with B-scan ultrasound studies in infants. The depth of the internal carotid artery (ICA) terminal division into ACA and MCA was closely correlated for both groups. In adults, it was found at 5.6 +/- 1.0 cm using TPDU while in cadavers it was found at 5.3 +/- 0.5 cm from the temporal bone. In infants, it was found at 3.2 +/- 0.3 cm for the right side, and 3.2 +/- 0.2 cm for the left side using TPDU, and at 3.4 +/- 0.4 cm and 3.4 +/- 0.5 cm for right and left sides respectively using B-scan ultrasound. The mean depth of the MCA mid-point in infants as defined by TPDU and B-scan was also closely correlated, with values of 2.8 +/- 0.3 cm and 2.7 +/- 0.3 cm for right and left sides respectively using TPDU and of 2.8 +/- 0.4 cm and 2.7 +/- 0.4 cm for right and left sides respectively using B-scan ultrasound. Values for the most lateral part of the MCA did not correlate. In adults, signals from the ACA and PCA were obtained at greater SV depth than the MCA, thus preventing confusion.